Help with Third-order linear ordinary differential equation

OK here is my problem:

$\displaystyle y''' - y'' - 2y' = 0$

And these are my steps

$\displaystyle m^3 - m^2 - 2m = 0$

$\displaystyle m(m^2 - m - 2) = 0$

$\displaystyle m(m + 1)(m - 2) = 0$

$\displaystyle m = -1, 0, 2$

*C1, C2, C3 = Csub1, Csub2, Csub3

y = C1e^0x + C2e^2x + C3e^-x

solution: y = C1 + C2e^2x + C3e^-x

but when checking the problem on Wolfram Alpha, the solution is:

y = C1 + (1/2)C2e^2x + C3(-e^-x)

Is there a step I'm missing?